Ferroptosis in kidney disease: a bibliometric analysis from 2012 to 2024 - Hu, Yuxin; Tang, Jingyi; Hong, Hanzhang; Chen, Yexin; Ye, Beibei; Gao, Ziheng; Zhu, Gegongming; Wang, Lin; Liu, Weijing; Wang, Yaoxian (Frontiers in Pharmacology, 2025)
Background and aimsFerroptosis, a novel concept of programmed cell death proposed in 2012, in kidney disease, has garnered significant attention based on evidence of abnormal iron deposition and lipid peroxidation damage in the kidney. Our study aim to examine the trends and future research directions in the field of ferroptosis in kidney disease, so as to further explore the target or treatment strategy for clinical treatment of kidney disease.Material and MethodsA thorough survey using the Web of Science Core Collection, focusing on literature published between 2012 and 2024 examining the interaction between kidney disease and ferroptosis was conducted. VOSviewer, CiteSpace, and Biblioshiny were used for in-depth scientometric and visualized analyses.ResultsFrom 2012 to 2024, a total of 2,244 articles met the inclusion criteria for final analysis. The number of annual publications in this area of study showed a steady pattern at the beginning of the decade. The top 3 journals with the highest publication output were Renal Failure, Oxidative Medicine And Cellular Longevity, and Biomedicine & Pharmacotherapy. China and the United States had the highest number of publications. Central South University and Guangzhou Medical University as the most active and influential institutions. Documents and citation analysis suggested that Andreas Linkermann, Jolanta Malyszko, and Alberto Ortiz are active researchers, and the research by Scott J. Dixon and Jose Pedro Friedmann Angeli, as the most cited article, are more important drivers in the development of the field. Keywords associated with glutathione, lipid peroxidation, and nitric oxide had high frequency in the early studies. In recent years, however, there has been a shift towards biomarkers, inflammation and necrosis, which indicate current and future research directions in this area.ConclusionThe global landscape of the ferroptosis research in kidney disease from 2012 to 2024 was presented. Basic research and mechanism exploration for renal fibrosis and chronic kidney disease may be a hot spot in the future.